Hubungan Beban Kerja dengan Stres Kerja Tenaga Kesehatan Masyarakat di Puskesmas Kota Pekalongan - Ardiana Priharwanti; Teguh Irawan; Nida Mafaza Zulfa; Muflihatun Ni’mah; Tiara Anisa Salma; Isna Wida Khafidho; Nur Isnaeni; Iqro Ciciani; Muhammad Labib (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
Work stres is a state of physical imbalance that causes physical and psychological tension that affects the way of thinking, emotions and working conditions. Work stres among health workers is quite high, as are the public health workers who work in puskesmas. Work stres affects the workload which is too high. The influencing factor is the workload. The purpose of this research is to find out whether there is a relationship between workload and work stres in public health workers at the Pekalongan City Health Center. This study used a quantitative method with a sample of 26 public health workers in 14 Community Health Centers in Pekalongan City. Based on the results of the analysis of the Pearson Correlation Test, a significant value (p) was obtained between workload and work stres which was 0.019 or p-value <0.05. If you look at the interpretation above, the test results show that the test results stated that there was a significant relationship or that there was a relationship between workload and work stres in public health workers at the Pekalongan City Health Center.